Brain and Hepatic Glucose Utilization in Malarial Infection Does Not Depend on Cerebral Symptoms of the Disease. (19th December 2019) - Ghosh, Soumita; Sengupta, Arjun; Sharma, Shobhona; Sonawat, Haripalsingh M.
Abstract : Cerebral malaria causes several deaths every year. Global metabolic alteration, specifically hypoglycemia and lactic acidosis are hallmarks of severe malaria. Glucose being the major fuel source for the brain, it is important to understand cerebral glucose utilization in the host during cerebral complications of the disease that may have a significant role in cerebral pathogenesis. We have used 13 C NMR spectroscopy to understand glucose utilization in the brain and liver of mice with cerebral malaria (CM), noncerebral malaria (NCM), and in control mice. Animals were challenged with intravenous glucose bolus followed by metabolic profiling of brain and liver extracts. Our result suggests a differential glucose utilization in the malaria group with respect to that of controls, while no difference between CM and NCM.